(untitled) (American Journal of Islam and Society, 1994)
The Twenty-Second Annual Conference of the Association of Muslim Social Scientists (AMSS) was jointly organized by the Intemational Institute of Islamic Thought (IIIT) and the AMSS and was held at the IIIT premises in Hemdon, VA. The open-theme conference featured eighteen panels organized into fourtem sessions. The opening session consisted of the welcoming address by Dilnawaz Siddiqui, President (Clarion University of Pennsylvania, Clarion, PA), remarks by Mushtaqur Rahman, Conference Chairman (University of Iowa, Ames, IA), and the inaugural address of Taha al ’Alwani (President, IIIT). The second session, "Islamic Philosophy and Compamtive Approaches," was chaired by Ja’afar Sheikh Idris (Institute of Islamic and Arabic Sciences, Fairfax, VA). Presentations included "Islamic Theory of Knowledge: A Reapptaisal" by Sirajul Husain (Islamic Research and Development Council, Cleveland, OH), "Islamization of the Creative Imagination and Its Ramifications in the Visual Arts of Islam" by Halide A. Salam (Radford University, Radford, VA), and "The Concept of Free Will in the Comments of al Ash’ari, al Hilli, and Taftazani" by Anne E. Francisse (Seattle, WA). The third session had two concurrent panels: "Concept of Shzird and Democracy in Islam," chaited by Mumtaz Ahmad (Hampton University, Hampton, VA) and "Culture and Communication," chaired by Ali Ramadan (IIIT). The first panel comprised Aziza a1 Hibri (University of Richmond, Richmond VA) and Ja’afar Shaikh Idris. Al Hibri pointed out that shura (mutual consultation) is part of Islamic constitutional theory and reflects the divine dimension of an Islamic political framework-while democracy is one process of shzirti reflecting the human will in the political plane. Also featured was Hamid al-Ghazali (Islamic Center of Lawrence, Lawrence, MO), who gave a special report on the removal of an unjust leader from an Islamic institution that had been presented to the Circuit Court of Jackson County, Missouri. The culture and communication panel had three presentors. Shamf Rahman (Northern State Univedty, Aberdeen, SD) spoke on media types and Muslim culture vis-8-vis Pakistani films and videos. Hussein Abiva (Chicago, IL) dealt with the role and importance of Sufi orders in Balkan ...